Visual detection of 8-OHdG based on the aggregation of gold nanoparticles capped with the anti-8-OHdG antibody. Issue 19 (7th October 2015) - Wu, Liping; Pu, Wendan; Liu, Yue; Zhao, Huawen; Shu, Weiqun
<x xml:space="preserve">Abstract</x> AuNPs, capped with anti-8-OHdG antibody, aggregate when 8-OHdG was added, resulting in color change and redshift of absorption wavelength. So a simple and rapid method to selectively determine 8-OHdG was developed and semi-quantitative determination could be achieved by the naked eye.